Method of computation of energies in the fractional quantum Hall effect regime - Ammar, M.A.; Bentalha, Z.; Bekhechi, S. (Condensed Matter Physics, 2016)
In a previous work, we reported exact results of energies of the ground state in the fractional quantum Hall
effect (FQHE) regime for systems with up to Nе = 6 electrons at the filling factor ν = 1/3 by using the method of
complex polar coordinates. In this work, we display interesting computational details of the previous calculation
and extend the calculation to Ne = 7 electrons at ν = 1/3. Moreover, similar exact results are derived at the
filling ν = 1/5 for systems with up to Ne = 6 electrons. The results that we obtained by analytical calculation
are in good agreement with their analogues ones derived by the method of Monte Carlo in a precedent work. У попереднiй роботi ми отримали точнi результати для енергiй основного стану у режимi дробового квантового ефекта Холла (FQHE) для систем з Ne = 6 електронiв включно при коефiцiєнтi заповнення ν = 1/3,
використавши метод комплексних полярних координат. В цiй роботi ми представляємо цiкавi обчислювальнi деталi попереднiх розрахункiв i розширюємо нашi обчислення до Ne = 7 електронiв при ν = 1/3.
Крiм того, отримано подiбнi точнi результати при заповненнi ν = 1/5 для систем з Ne = 6 електронiв
включно. Отриманi результати за допомогою аналiтичних обчислювань добре узгоджуються з їхнiми
аналогами, отриманими методом Монте Карло в данiй роботi.